Building hematite nanostructures by oriented attachment - Lou, David Xiong Wen (2012)
Getting bigger: Oriented attachment takes place among large hematite nanocrystals with a size over 100 nm to form 2D assemblies that further assemble into 3D superstructures through dipole–dipole interactions. Based on shape selectivity, 1D nanorods can be assembled into 3D quasi nanocubes by oriented attachment.